PENGARUH TAX INCENTIVE, POLITICAL COST DAN PENILAIAN EKUITAS TERHADAP KONSERVATISME AKUNTANSI: ( Studi Empiris Pada perusahaan Manufaktur Sub Sektor Makanan dan Minuman Yang Terdaftar di Bursa Efek Indonesia tahun 2018-2022) - Adjie, Shiva Destiani; Syamsul Asmedi (Perwira Journal of Economics & Business, 2023)
This study aims to test and prove empirically about tax incentive, political cost and equity valuation on accounting conservatism partially or simultaneously. The independent variables in this study are tax incentive, political cost and equity valuation, the dependent variable used is accounting conservatism. The population in this study were food and beverage sub-sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 research period. The sampling technique in this study used purposive sampling. The total companies sampled were 13 companies, the analysis method used linear and logistic regression. Based on the partial test results, it shows that tax incentive, political cost has a significant positive effect on accounting conservatism, while equity valuation has no significant effect on accounting conservatism. Simultaneously, the independent variables of tax incentive, political cost, and equity valuation affect the dependent variable of accounting conservatism with a Nagerkelke R Square value of 14%.